Friendship and Rhetoric in the Middle Ages The Linguistic Performance of Intimacy from Cicero to Aelred. - McDonie, R. Jacob ([S.l.] : ROUTLEDGE, 2019)
Friendship and Rhetoric in the Middle Ages:The Linguistic Performance of Intimacy from Cicero to Aelred covers approximately 1,200 years of literature. This is a book on "medieval literature" that foregrounds language as the agent for cultivating medieval friendship (from the first century BC to c. 1160 AD) in oratorical, ecclesiastical, monastic, and erotic contexts. Taking a different approach than many works in this area, which search for the lived experience of friends behind language, this book stands apart in looking at friendship's enactment through rhetorical language among classical and medieval authors.
OCLC-licensed vendor bibliographic record.
Keywords: LITERARY CRITICISM / Medieval; FAMILY & RELATIONSHIPS / General; Friendship; Philosophy, Medieval